IJCM_85A: Prevalence of unmet need for contraception among married women aged 15-49 years in urban and rural areas of Telangana. - Stefi M S; Darivemula Surendra Babu; Tondare Devidas P (Wolters Kluwer Medknow Publications, 2024)
Background: As reported by NFHS 5, over seventy percent of presently married women aged 15-49 have a demand for family planning. Women encounter a multitude of obstacles when it comes to accessing and adopting contraception, including limited knowledge, social disapproval, and inadequate availability of family planning resources. Objective: The aim of this study is to estimate the prevalence of unmet need for contraception and factors affecting contraceptive behaviour among reproductive age group women aged 15-49 years living in urban and rural areas of Telangana. Methodology: A cross-sectional study was conducted in urban and rural areas of Telangana among 306 reproductive age group women aged 15-49 years. Data was collected using a structured questionnaire and chi-square test was used to assess the significance. Results: The unmet need for contraception was found to be 18.6%, and it was significantly higher in urban than in rural (24.2% and 13.1% respectively). Spacing need was 6.2% and limiting need was 12.4%, significantly higher among urban (17%) than in rural (7.8%). Occupation of the correspondent was found to be significantly associated with an unmet need for contraception. Conclusion: A high unmet need for contraception was observed among women in Telangana, highlighting the existence of a knowledge-action gap in promoting positive attitudes and behaviours toward contraception. Further research is necessary to explore the underlying factors contributing to the rising unmet need and training of frontline healthcare workers to raise awareness about family planning methods and address associated stigmas.